Analysis Of Public Satisfaction Index In Public Services In Pagar Gunung Village, Padang Guci Hulu District, Kaur District - Candra Adi Putra Putra; Ahmad Soleh; Yun Fitrano (Penerbit Jurnal Indonesia, 2023)
The aim of the study was to analyze the community satisfaction index on public services at the Pagar Gunung Village Office, Padang Guci Hulu District, Kaur District. The data analysis technique used was to measure the value of the Community Satisfaction Index (IKM) based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017. The sample in this study was 155 people from Pagar Gunung Village, Padang Guci Hulu District, Kaur Regency who received services from the Pagar Gunung Village Office, Padang Guci Hulu District, Kaur District. The Community Satisfaction Index (IKM) for service quality at the Pagar Gunung Village Office, Padang Guci Hulu District, Kaur Regency obtained an average value of 3.20 which is a good assessment. Furthermore, the IKM of service units is multiplied by 25 so that the IKM in Pagar Gunung Village Office, Padang Guci Hulu District, Kaur Regency is 80.07 with service quality B with good criteria because it is in the value interval of 76.61 – 88.30. The element of cost/tariff gets the highest rating with an average score of 3.63 with very good assessment criteria. This illustrates that the community views the Pagar Gunung Village Office, Padang Guci Hulu District, Kaur District as providing services free of charge. The lowest satisfaction score is 2.54, namely the completion time with poor assessment criteria. This illustrates that the time required for the completion of documents is not as promised, due to the slowness of employees in providing services, inadequate requirements and the Village Head who is often not present.